2018
DOI: 10.1212/wnl.0000000000004798
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations of the Global Multiple System Atrophy Research Roadmap Meeting

Abstract: Multiple system atrophy (MSA) is a rare neurodegenerative disorder with substantial knowledge gaps despite recent gains in basic and clinical research. In order to make further advances, concerted international collaboration is vital. In 2014, an international meeting involving leaders in the field and MSA advocacy groups was convened in Las Vegas, Nevada, to identify critical research areas where consensus and progress was needed to improve understanding, diagnosis, and treatment of the disease. Eight topic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…It has also been postulated that LC burden precedes substantia nigra involvement in Parkinson’s disease (Zarow et al , 2003; Braak et al , 2004; Seidel et al , 2015), rendering the LC a good candidate for preclinical diagnosis (Liu et al , 2017). However, the field lacks a comprehensive analysis detailing the stages of neuronal loss in Parkinson’s disease.Multiple system atrophy (MSA) is another heterogeneous α-synucleinopathy, in which autonomic dysfunction, parkinsonism, and ataxia (Stankovic et al , 2014; Walsh et al , 2018) are associated with severe neuronal loss in the LC and noradrenergic cardiorespiratory brainstem nuclei (A5, A1) (Benarroch et al , 2008). An in vivo neuromelanin-sensitive MRI study has shown that LC contrast is reduced in MSA compared to healthy controls and that the ratio of neuromelanin-sensitive MRI contrast in substantia nigra versus LC could help distinguish MSA from Parkinson’s disease (Matsuura et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been postulated that LC burden precedes substantia nigra involvement in Parkinson’s disease (Zarow et al , 2003; Braak et al , 2004; Seidel et al , 2015), rendering the LC a good candidate for preclinical diagnosis (Liu et al , 2017). However, the field lacks a comprehensive analysis detailing the stages of neuronal loss in Parkinson’s disease.Multiple system atrophy (MSA) is another heterogeneous α-synucleinopathy, in which autonomic dysfunction, parkinsonism, and ataxia (Stankovic et al , 2014; Walsh et al , 2018) are associated with severe neuronal loss in the LC and noradrenergic cardiorespiratory brainstem nuclei (A5, A1) (Benarroch et al , 2008). An in vivo neuromelanin-sensitive MRI study has shown that LC contrast is reduced in MSA compared to healthy controls and that the ratio of neuromelanin-sensitive MRI contrast in substantia nigra versus LC could help distinguish MSA from Parkinson’s disease (Matsuura et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple system atrophy (MSA) is another heterogeneous α-synucleinopathy, in which autonomic dysfunction, parkinsonism, and ataxia (Stankovic et al , 2014; Walsh et al , 2018) are associated with severe neuronal loss in the LC and noradrenergic cardiorespiratory brainstem nuclei (A5, A1) (Benarroch et al , 2008). An in vivo neuromelanin-sensitive MRI study has shown that LC contrast is reduced in MSA compared to healthy controls and that the ratio of neuromelanin-sensitive MRI contrast in substantia nigra versus LC could help distinguish MSA from Parkinson’s disease (Matsuura et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is usually not until the advanced stages of the disease that autonomic failure and urogenital dysfunction become apparent (9, 10), which then, in addition to poor levodopa response, allow for the diagnosis of probable or possible MSA according to the current diagnostic criteria (11). Due to the diagnostic challenges in the early phase of the disease, emphasis has been put on identifying premotor symptoms to improve diagnostic accuracy on one hand and delineate MSA from PD or other lookalikes on the other (6, 12, 13). The European MSA study group (EMSA-SG) developed a red flag check list and analyzed the prevalence of 22 clinical features in 74 MSA and 116 PD patients (14).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, UMSARS, the primary outcome measure in the large majority of all previous trials, should be revised and improved on the model of what was achieved in the field of PD more than 10 years ago, moving from the "historical" Unified PD Rating Scale (UPDRS) to the MDS-UPDRS. 159,160 Functional and device-based outcomes should also be developed and properly validated, thereby providing additional and possibly more sensitive study end points. Finally, as our understanding of the natural history of MSA improves, it will be possible to identify more homogeneous clusters of patients and to predict their progression if not their response to given therapies.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…The capacity to conduct clinical trials will further improve in the future as centers will be better organized, patients better informed, and national and international networks better structured to facilitate recruitment. In addition, UMSARS, the primary outcome measure in the large majority of all previous trials, should be revised and improved on the model of what was achieved in the field of PD more than 10 years ago, moving from the “historical” Unified PD Rating Scale (UPDRS) to the MDS‐UPDRS . Functional and device‐based outcomes should also be developed and properly validated, thereby providing additional and possibly more sensitive study end points.…”
Section: Diagnosismentioning
confidence: 99%